POLYPHARMACY AND FRAILTY AMONG WORLD TRADE CENTER GENERAL RESPONDERS. (20th December 2022) - Hung, William; Bello, Ghalib; Ko, Fred; Sabra, Ahmad; Thanik, Erin; Lucchini, Roberto; Ornstein, Katherine
Abstract: Polypharmacy in older adults is associated with increased risk of adverse events such as falls, adverse drug reactions and functional decline. WTC responders suffer from conditions related to WTC exposure and are at higher risk of polypharmacy. We examined patterns of medication use among WTC general responders aged 50 and over who had at least one visit from 2017 to 2019 (n=7, 679); 56.1% took 5+ medications and 22.5% took 10+ medications. Factors associated with polypharmacy (taking 5+ medications) include age (OR 1.08, p<0.001), female sex (OR 1.33, p<0.001), obesity (1.90, p<0.001), fair/poor self-rated health (OR 1.32, p<0.001) and limitations on performing moderate activity (OR 1.52, p<0.001). Frailty, as measured by the deficit count in the Clinical Frailty Index, is associated with polypharmacy after adjusting for other covariates (OR 1.23, p<0.001). Addressing polypharmacy by improving medication use may yield health benefits for this rapidly aging population at risk for adverse outcomes.